Equine diseases published in the weekly epidemiological reports of the National Agrarian Health Service of Peru during the period 2010–2018 - Moscoso, Marcel (2021)
The objective of the study was to describe the cases of diseases in equines published in the weekly epidemiological reports made by the epidemiological surveillance system of the National Agrarian Health Service of Peru (SENASA) during the period 2010–2018. Confirmed cases of equine diseases were collected and classified, which were summarized using descriptive statistics. A total of 185 notifications of suspected cases were found, of which 75 were positive for different diseases in equines. These were venezuelan equine encephalomyelitis, vesicular stomatitis, New World screwworm, leptospirosis and rabies; the last one showing an endemic character due to its presence in different departments and in all the years of study, adding a total of 66 positive notifications, while the others only correspond to sporadic outbreaks. The study demonstrated the presence of diseases in equines that affect their livestock productivity and have zoonotic potential, in addition to reports of suspected exotic diseases that do not exist in the country, so it is necessary to notify SENASA of all cases of infectious diseases and epidemiological surveillance of disease cases in this animal population.